Pengaruh Penerapan Cerobong Surya terhadap Kelajuan Udara Koridor pada Bangunan Inner-Court - Dede Irwan; Dian Perwita Sari (Vokasi, 2018)
The achievement of thermal comfort in damp hot tropical climate such as Pontianak city becomes difficult to be achieved due to having problems such as high temperature of air; humidity of air; solar radiation and low average speed of air movement. The main way to get thermal comfort is to decrease heat by continuously improving natural air movement using natural ventilation both horizontally and vertically. The solar chimney with a tromble wall can be utilized as a form of soft technology, which tackles climate as a beneficial factor for thermal comfort in a building. The solar chimney with a tromble wall can create a temperature difference at the top and bottom of the building so that vertical ventilation occurs. Prototype solar chimney with tromble wall is one way to get thermal comfort in the building. The results show that the air speed at Inner court without sun chimneys is lower than 0.08 m / s from Inner court with a solar chimney of 0.18 m / s. The difference between the air velocity between Inner court without solar chimney with Inner court with solar chimney that is equal to 0.10 m / s. Air speed at Inner court with solar chimney 113.16% higher than Inner court without solar chimneys.